2013
DOI: 10.1080/09603123.2013.857393
|View full text |Cite
|
Sign up to set email alerts
|

Rice consumption and urinary concentrations of arsenic in US adults

Abstract: Exposure to inorganic arsenic in the general population occurs mainly from drinking water and food sources. This study examined the association between rice consumption and urinary concentrations of arsenic in US adults, aged 20-85 years, in the 2003-2006 National Health and Nutrition Examination Survey. Significantly higher geometric means of creatinine-corrected urinary concentrations of total arsenic (TAs) and dimethylarsinic acid (DMA) were found in participants who consumed rice more than twice per week, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 39 publications
5
25
1
Order By: Relevance
“…However, Jain (2014) did find male nonsmokers to have higher unadjusted means than female nonsmokers for UAB, UAS, as well as UDMA. In order to interpret results from this study and the studies by Jain (2014) and Wei et al (2014), the differences in study design must be considered. Jain's (2014) study was done on nonsmokers only using data from NHANES for 2003-2010 while, the aim of the study by Wei et al (2014) was primarily to assess association between rice consumption and arsenic.…”
Section: Impact Of Gender and Race/ethnicitymentioning
confidence: 96%
See 3 more Smart Citations
“…However, Jain (2014) did find male nonsmokers to have higher unadjusted means than female nonsmokers for UAB, UAS, as well as UDMA. In order to interpret results from this study and the studies by Jain (2014) and Wei et al (2014), the differences in study design must be considered. Jain's (2014) study was done on nonsmokers only using data from NHANES for 2003-2010 while, the aim of the study by Wei et al (2014) was primarily to assess association between rice consumption and arsenic.…”
Section: Impact Of Gender and Race/ethnicitymentioning
confidence: 96%
“…In order to interpret results from this study and the studies by Jain (2014) and Wei et al (2014), the differences in study design must be considered. Jain's (2014) study was done on nonsmokers only using data from NHANES for 2003-2010 while, the aim of the study by Wei et al (2014) was primarily to assess association between rice consumption and arsenic. Both in this study and in the study by Jain (2014), NHW were found to have the lowest AGM for UAB, UAS, and UDMA and unclassified race/ethnicities had the highest AGM.…”
Section: Impact Of Gender and Race/ethnicitymentioning
confidence: 96%
See 2 more Smart Citations
“…In populations with high seafood intakes, assessment of iAs using biomarkers is difficult because some nontoxic seafood arsenicals contribute to DMA and total arsenic concentrations in urine. Previous epidemiologic studies have relied on methods such as excluding participants who reported recent seafood intake or adjusting for seafood intake (using self-reported seafood intake or urine arsenobetaine) in regression models (54,55). In populations with high seafood intakes, excluding participants who report recent seafood consumption is problematic.…”
Section: Discussionmentioning
confidence: 99%